2022
DOI: 10.1093/geront/gnac111
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Falls Among Older Adults in Primary Care: A Mixed Methods Process Evaluation Using the RE-AIM Framework

Abstract: Background and Objectives Falls are a leading cause of injuries and injury deaths for older adults. The Centers for Disease Control and Prevention’s Stopping Elderly Accidents Deaths and Injuries (STEADI) initiative, a multifactorial approach to fall prevention, was adapted for implementation within the primary care setting of a health system in upstate New York. The purpose of this paper is to: (a) report process evaluation results for this implementation using the Reach, Effectiveness, Adop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(21 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…Data-extraction of descriptive data showed that in seven studies ( 38 40 , 43 , 46 , 48 , 49 ), only health care professionals (e.g., physical therapists, general practitioners, pharmacists, allied health assistances, occupational therapists) were included. In the other studies, there was a combination of health care and social care professionals (e.g., informal care, social service workers) ( 41 , 47 ) and/or other professionals (e.g., clinical support staff, fitness leaders, practice site leaders, volunteers) ( 42 , 44 , 45 , 50 52 ). Furthermore, eleven studies ( 38 40 , 42 45 , 48 50 , 52 ) focused primarily on primary care as setting; the other four studies ( 41 , 46 , 47 , 51 ) concentrated on a broader community-based setting.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Data-extraction of descriptive data showed that in seven studies ( 38 40 , 43 , 46 , 48 , 49 ), only health care professionals (e.g., physical therapists, general practitioners, pharmacists, allied health assistances, occupational therapists) were included. In the other studies, there was a combination of health care and social care professionals (e.g., informal care, social service workers) ( 41 , 47 ) and/or other professionals (e.g., clinical support staff, fitness leaders, practice site leaders, volunteers) ( 42 , 44 , 45 , 50 52 ). Furthermore, eleven studies ( 38 40 , 42 45 , 48 50 , 52 ) focused primarily on primary care as setting; the other four studies ( 41 , 46 , 47 , 51 ) concentrated on a broader community-based setting.…”
Section: Resultsmentioning
confidence: 99%
“…In the other studies, there was a combination of health care and social care professionals (e.g., informal care, social service workers) ( 41 , 47 ) and/or other professionals (e.g., clinical support staff, fitness leaders, practice site leaders, volunteers) ( 42 , 44 , 45 , 50 52 ). Furthermore, eleven studies ( 38 40 , 42 45 , 48 50 , 52 ) focused primarily on primary care as setting; the other four studies ( 41 , 46 , 47 , 51 ) concentrated on a broader community-based setting. Ten studies ( 39 41 , 44 49 , 52 ) used qualitative approaches only, such as semi-structured interviews and focus groups, whereas five studies ( 38 , 42 , 43 , 50 , 51 ) applied mixed methods with a qualitative and quantitative approach (e.g., surveys and documents).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations